MADNESS AND GENDER: A STUDY OF MENTAL ILLNESS IN THE TEXT, A BOOK OF LIGHT - Khan, Saba (International Journal of Psychosocial Rehabilitation, 2020)
There is a wide variety of literature on mental illness mostly in western countries. Mental illness is widely stigmatized and is perceived in different manner in society since earlier times. There is lack of awareness of different kinds of mental illnesses in Asia and in other developing countries. Though people try to eschew to talk about their mental issues and are misinterpreted, awareness is being created in western countries through various ways and use of narratives can be said to be one of such means. Writers are contributing significantly to enlighten the society and helping those who are suffering from different categories of mental illnesses. People with psychological problem are usually misunderstood, which make them unable to seek help for their problem. This further distances them from their social links. Even closed ones fail to understand their sufferings and their condition, the reason being lack of knowledge of the malady in Indian society. Studies suggest that women are mostly affected by mental illness than men, as 'madness is a female malady because it is experienced by more women than men' (Showalter). This paper attempts to explore mental illness or madness in terms of gender in India through close reading of the book, A book of light written by Jerry Pinto.